A cross‐sectional study of 'care left undone' on nursing shifts in hospitals. (20th April 2016) - Ball, Jane E.; Griffiths, Peter; Rafferty, Anne Marie; Lindqvist, Rikard; Murrells, Trevor; Tishelman, Carol
Abstract: Aims: To determine factors associated with variation in 'care left undone' (also referred to as 'missed care') by Registered Nurses (RNs) in acute hospital wards in Sweden. Background: 'Care left undone' has been examined as a factor mediating the relationship between nurse staffing and patient outcomes. The context has not previously been explored to determine what other factors are associated with variation in 'care left undone' by RNs. Design: Cross‐sectional survey to explore the association of RN staffing and contextual factors such as time of shift, nursing role and patient acuity/dependency on 'care left undone' was examined using multi‐level logistic regression. Methods: A survey of 10, 174 RNs working on general medical and surgical wards in 79 acute care hospitals in Sweden (January–March 2010). Results: Seventy‐four per cent of nurses reported some care was left undone on their last shift. The time of shift, patient mix, nurses' role, practice environment and staffing have a significant relationship with care left undone. The odds of care being left undone is halved on shifts where RN care for six patients or fewer compared with shifts where they care for 10 or more. Conclusion: The previously observed relationship between RN staffing and care left undone is confirmed. Reports of care left undone are influenced by RN roles. Support worker staffing has little effect. Research is needed to identify how these factors relate to one another and whether care left undone is a predictor of adverse patient outcomes.